2012
DOI: 10.1158/1541-7786.mcr-11-0594
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 19q13 Nucleolar Zinc Finger Protein Suppresses Tumor Cell Growth through Inhibiting Ribosome Biogenesis and Inducing Apoptosis but Is Frequently Silenced in Multiple Carcinomas

Abstract: Epigenetic disruption of tumor suppressor genes is frequently involved in tumorigenesis. We identified a novel 19q13 KRAB domain-containing zinc finger protein, ZNF545/ZFP82, broadly expressed in normal tissues but downregulated in multiple tumor cell lines. The ZNF545 promoter contains a CpG island, which is frequently methylated in cell lines. The transcriptional silencing of ZNF545 could be reversed by pharmacologic or genetic demethylation, indicating direct epigenetic silencing. ZNF545 was also frequently… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…ZNF545 is reportedly a functional tumor suppressor in multiple cancers and is silenced by promoter methylation by our group [14], [26]. This is the first study to elucidate the direct relationship between ZNF545 and breast cancer.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…ZNF545 is reportedly a functional tumor suppressor in multiple cancers and is silenced by promoter methylation by our group [14], [26]. This is the first study to elucidate the direct relationship between ZNF545 and breast cancer.…”
Section: Discussionmentioning
confidence: 77%
“…Our previously studies have demonstrated that ZNF545 is frequently silenced by promoter methylation in multiple carcinomas including esophageal, nasopharyngeal, gastric, colorectal, and breast cancer [14], [26], [28]. To identify the relationship between the clinicopathological features and methylation status of ZNF545 in breast tumorigenesis, and to develop biomarkers for breast cancer detection and prognosis, ZNF545 methylation was examined in 29% of primary breast tumor tissues, but not in normal tissues, consistent with our previous study [14]. No significant associations were found between clinicopathological features and methylation status, although this needs to be further confirmed by studies using more samples.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Currently, it is well accepted that epigenetic alterations even precede genetic changes during tumorigenesis [3]. An increasing number of epigenetic silenced tumor suppressor genes (TSGs) were identified in multiple cancers [48], which exert antitumor effects but silenced by promoter methylation in tumor specific manner.…”
Section: Introductionmentioning
confidence: 99%